Factors associated with serum aflatoxin levels in pregnant women in Banke district, Nepal. - Ghosh, Shibani. (Tufts University. Tisch Library., 2016)
Dr. Shibani Ghosh examines aflatoxin levels in pregnant women in the Banke district of Nepal, with attention to their diets and most likely sources of aflatoxin exposure.; Nutrition School: NIL Symposium Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy